AGRICULTURAL TECHNOLOGY IN BRAZIL - Silva, Pedro Augusto dos Santos; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2023)
Agribusiness continues to rise in Brazil, especially in the pandemic, tons of products were exported, such as soy, coffee, sugar, among others, causing demand in production to increase. As a result, agricultural technologies have become essential to improve productivity and time optimization. In this context, the objective of the work is to verify through a bibliographical survey the agricultural technologies in force in Brazil, as well as the advantages of these resources to the rural producer and the entire population. It was possible to verify that nowadays the concept of Agriculture 4.0 predominates, which employs the main rural technologies, such as drones, wireless sensor network, internet of things, artificial intelligence, autonomous work and robotics. The results point to the positive use of agricultural technologies, in crop and climate monitoring, and in soil analysis, in real time and without the need to be in the field. However, some difficulties still need to be solved, such as the lack of internet connection in the field. Concluding that agricultural technologies are essential to meet the demand of farmer productions, and thus offer quality products to the population, with lower environmental impacts.
Keywords: Agriculture 4.0; Technological innovations; Productivity